Soldering in electronics assembly - Judd, Mike (Newnes, 1999)
Managers, engineers and technicians will use this book during industrial construction of electronics assemblies, whilst students can use the book to get a grasp of the variety of methods available, together with a discussion of technical concerns. It includes over 200 illustrations, including a photographic guide to defects, and contains many line drawings, tables and flow charts to illustrate the subject of electronics assembly. Soldering in Electronics Assembly looks theoretically at everything needed in a detailed study, but in a practical manner. It examines the soldering processes in the light of electronic assembly type; solder; flux; and cleaning requirements. It has information on every available process, from the most basic hand soldering through to latest innovatory ones such as inert atmosphere wave soldering and zoned forced convection infra-red machines. The book provides a detailed analysis of solder and soldering action; purpose of flux and relevant flux types for any application; classification of assembly variants; assessment and maintenance of solderability. There is also a detailed analysis of soldering process defects and causes. In addition, Soldering in Electronics Assembly contains a new chapter on Ball Grid Array (BGA) technology. Mike Judd is MD of Mike Judd Marketing and former MD of Electrovert UK, Director of Marketing Europe for Electrovert, part of the Cookson Group, and Director of OEM at Speedline. Keith Brindley is a technical author with a wealth of experience of all aspects of electronics technology. - A practical guide for the industry covering all the main soldering processes currently in use - Cleaning, faults, troubleshooting and standards are all major topics - Considers safety and solder process quality assessment.